2022
DOI: 10.1021/acs.joc.2c02431
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Coupling of ortho-Alkynylnaphthols and Benzofurans: [4 + 2] Cycloaddition and Friedel–Crafts Reaction

Abstract: Catalytic direct [4 + 2] cycloaddition reactions and Friedel−Crafts reactions of ortho-alkynylnaphthols with benzofurans have been developed, affording functionalized hydrobenzofuro[3,2-b]chromans and hydroarylation products, respectively, in high yields with high chemoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Moreover, unlike indole as a reactive nucleophile with multi‐reactive sites (N1, C2 and C3), the Friedel‐Crafts reaction adducts of furan have usually been observed as minor by‐product, [10b] and there are limited reports of the formal furan‐attack reaction of ortho ‐alkynylnaphthols. Recently, we developed an chiral Brønsted acid C6 ‐catalyzed [4+2] cycloaddition of ortho ‐alkynylnaphthol with benzofuran to obtain the cycloadduct in 67% yield and with 74% ee, which was treated by the binary acid Sc(OTf) 3 /diphenyl phosphate (DP) , the 1,4‐adduct could be obtained in 93% yield and with 74% ee (Scheme 1A) [11] . Very recently, Pan and coworkers reported that chiral phosphoric acid (CPA) A1 catalyzed the reaction of ortho ‐alkynylnaphthols with in situ generated furans, giving furan‐embedded styrene atropisomers with moderate enantioselectivity (up to 70% ee) (Scheme 1B) [12] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, unlike indole as a reactive nucleophile with multi‐reactive sites (N1, C2 and C3), the Friedel‐Crafts reaction adducts of furan have usually been observed as minor by‐product, [10b] and there are limited reports of the formal furan‐attack reaction of ortho ‐alkynylnaphthols. Recently, we developed an chiral Brønsted acid C6 ‐catalyzed [4+2] cycloaddition of ortho ‐alkynylnaphthol with benzofuran to obtain the cycloadduct in 67% yield and with 74% ee, which was treated by the binary acid Sc(OTf) 3 /diphenyl phosphate (DP) , the 1,4‐adduct could be obtained in 93% yield and with 74% ee (Scheme 1A) [11] . Very recently, Pan and coworkers reported that chiral phosphoric acid (CPA) A1 catalyzed the reaction of ortho ‐alkynylnaphthols with in situ generated furans, giving furan‐embedded styrene atropisomers with moderate enantioselectivity (up to 70% ee) (Scheme 1B) [12] .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we developed an chiral Brønsted acid C6-catalyzed [4 + 2] cycloaddition of orthoalkynylnaphthol with benzofuran to obtain the cycloadduct in 67% yield and with 74% ee, which was treated by the binary acid Sc(OTf) 3 /diphenyl phosphate (DP), the 1,4-adduct could be obtained in 93% yield and with 74% ee (Scheme 1A). [11] Very recently, Pan and coworkers reported that chiral phosphoric acid (CPA) A1 catalyzed the reaction of ortho-alkynylnaphthols with in situ generated furans, giving furanembedded styrene atropisomers with moderate enantioselectivity (up to 70% ee) (Scheme 1B). [12] Interestingly, when naphthol[1,2-b]furans were employed instead of benzofurans, the chiral Brønsted acid C6 catalyzed reactions with ortho-alkynylnaphthols afforded chiral 1,4-adducts in 67 to 93% yield and with 34% to 96% ee, and no [4 + 2] cycloadducts were observed (Scheme 1C).…”
mentioning
confidence: 99%